“Banana Canaan Sodindo : a biography - Mashingaidze, Terence M. (Oxford University Press, 2016)
Banana, Canaan Sodindo (1936-2003), nationalist politician, first titular president of independent Zimbabwe, statesman, peace broker, clergyman, author, soccer administrator, academic, poet, and journalist, was born on 5 March 1936 at Esiphezini. in Essexvale, now Esigodini, District near Bulawayo in Southern Rhodesia.